1999
DOI: 10.4269/ajtmh.1999.60.1041
|View full text |Cite
|
Sign up to set email alerts
|

Limited potential for mosquito transmission of genetically engineered, live-attenuated Venezuelan equine encephalitis virus vaccine candidates.

Abstract: Abstract. In an attempt to improve the current live-attenuated vaccine (TC-83) for Venezuelan equine encephalitis (VEE), specific mutations associated with attenuation of VEE virus in rodent models were identified. These mutations were inserted into full-length cDNA clones of the Trinidad donkey strain of VEE virus by site-directed mutagenesis, and isogenic virus strains with these mutations were recovered after transfection of baby hamster kidney cells with infectious RNA. We evaluated 10 of these strains for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Based on our results in non-human primates and those from cohort studies in rodents [17,[28][29][30] and mosquitoes [32], V3526 was selected for development into a human-use vaccine. These other studies, like this study, showed V3526 to be more safe, immunogenic and efficacious than TC-83, and without any indication of reversion to virulent phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results in non-human primates and those from cohort studies in rodents [17,[28][29][30] and mosquitoes [32], V3526 was selected for development into a human-use vaccine. These other studies, like this study, showed V3526 to be more safe, immunogenic and efficacious than TC-83, and without any indication of reversion to virulent phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the infection rate for theIAB/IDE2 construct did differ significantly (P ϭ 0.1) from that of the IAB parent. The lack of statistical significance between parental IAB and ID viruses could be the result of small sample sizes or extensive cell culture passaging (6-Vero and 1-BHK) of the IAB virus used to generate the VEE/IC-109 clone; cell culture passage is known to reduce mosquito infectivity by subtype IAB VEEV (27). In contrast, virus from the subtype IC clone p3908acb (generated from a virus that had been passaged only once in mosquito cells) infected mosquitoes at a higher (P ϭ 0.08) rate, 84% at 7.1 log 10 PFU/ml (Table 1), than the enzootic ID virus, also of low passage (once in suckling mice and once in Vero cells).…”
mentioning
confidence: 99%
“…It is also possible that lack of knowledge of mutation(s) of viral genes, which can affect the virulence of the virus, might have contributed to their conclusion. [37][38][39][40][41] In addition, the possibility of infection due to increased severity of tissue tropism cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%